2012
DOI: 10.1590/s2176-94512012000600017
|View full text |Cite
|
Sign up to set email alerts
|

Class II malocclusion with deep overbite: a sequential approach

Abstract: Objective: The aim of this case report was to evaluate the results of deep overbite correction by the segmented arch technique. Methods: The first stage of the treatment was performed with this technique to intrude incisors and canines. A maxillary transpalatal bar and a mandibular lingual arch using 0.051-in archwire were employed associated to a facial bow, anchored primarily with occipital pull and, after molar relationship correction, changed to high pull. Results: Upper incisors presented a great amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…The anti-clockwise rotation during puberal growth spurt, representative of brachiocephalic pattern, was not observed probably due the molar extrusions, corroborating with the studies of some authors [13][14][15][16][17][18][19] . The total cephalometric superimposition between T 0 and T 1 of Group 2 showed forward displacement and anticlockwise rotation of the mandible, together with profile improvement.…”
supporting
confidence: 87%
See 4 more Smart Citations
“…The anti-clockwise rotation during puberal growth spurt, representative of brachiocephalic pattern, was not observed probably due the molar extrusions, corroborating with the studies of some authors [13][14][15][16][17][18][19] . The total cephalometric superimposition between T 0 and T 1 of Group 2 showed forward displacement and anticlockwise rotation of the mandible, together with profile improvement.…”
supporting
confidence: 87%
“…Nevertheless, in the mandibular arch molar intrusion was observed to decrease the Spee curve, contributing for an average 0.4 º decrease of SN.GoGn and anti-clockwise rotation of the mandible (Tables 2 and 3) (Figure 6). These data were corroborated by Baccetti et al 15 and Martinelli et al 19 , who reported that the overbite correction resulted of the intrusion of maxillary incisors as well as mandibular incisors accompanied by mandibular growth.…”
supporting
confidence: 62%
See 3 more Smart Citations